Effects of Preoperative Oral Carbohydrate on Perioperative Maternal Outcomes Undergoing Cesarean Section: A Systematic Review and Meta-Analysis - Haibin Shi; Caihong Zheng; Bin Zhu (Anesthesiology Research and Practice)
Purpose. Preoperative oral carbohydrate (CHO) is a rapid postoperative rehabilitation protocol that improves perioperative outcomes and is widely used in adult surgical patients. However, pregnant women are excluded because of the possibility of aspiration due to delayed gastric emptying. This meta-analysis was conducted to evaluate the efficacy of preoperative oral CHO in elective cesarean section. Methods. PubMed, Embase, Web of Science, and the Cochrane Library were searched from inception to July 2023. Randomized controlled trials were included. The risk of bias was assessed using the Cochrane tool. Risk ratios and 95% confidence intervals were calculated. Meta-analysis was performed using random-effects models to estimate risk ratios and mean differences (MDs) with 95% confidence intervals (CIs). The outcomes included thirst and hunger scores, incidence of vomiting and nausea, time to flatus, and homeostatic model assessment of insulin resistance (HOMA-IR). Results. A total of nine studies with 1211 patients were included in the analysis. The levels of thirst and hunger were evaluated using a 10-point visual analog scale, with 0 representing the best and 10 representing the worst. The severity of hunger (weighted mean difference (WMD: −2.34, 95% CI: −3.13 to −1.54), time to flatus (WMD: −3.51 hours, 95% CI: −6.85 to −0.17), and HOMA-IR (WMD: −1.04, 95% CI: −1.31 to −0.77) were significantly lower in the CHO group compared to the control group. However, there were no significant differences in the severity of thirst or the incidence of vomiting and nausea between the CHO and control groups. Conclusion. Preoperative oral CHO during cesarean section alleviates thirst and hunger, shortens the time of postoperative flatus, and reduces HOMA-IR. However, the available evidence is insufficient to reach a clear consensus on the benefits or harms of preoperative oral CHO during cesarean section. Therefore, it is premature to make a definitive recommendation for or against its routine use.